2023
DOI: 10.1007/s13399-022-03671-y
|View full text |Cite
|
Sign up to set email alerts
|

Power Biomass to Liquid — an option for Europe’s sustainable and independent aviation fuel production

Abstract: The European Union guides its member states to a gradual uptake of sustainable aviation fuel (SAF) from 2% vol. in 2025 to 63% vol. by 2050 with the ReFuelEU proposal as part of the Fit-for-55 package. A promising production pathway for SAF presents itself in the Power Biomass to Liquid (PBtL) process, which converts non-crop-based biomass residue and renewable power via the Fischer–Tropsch route. In this study, a techno-economic and greenhouse gas (GHG) emission analysis of a small-scale (50 MWth) PBtL proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Nevertheless, the availability of enough electrolyzer units might prove to be a bottleneck for the process roll-out. 78 Further, the simplified approach for the integration scenarios, as described in Section 2.7.3, should only be understood as an approximation of the actual costs for the integration of fluctuating renewable energy sources. A more accurate process design would include a cost-optimised design of the power production system (mix of wind and PV), the electrolyzer and the hydrogen storage system depending on local boundary conditions.…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, the availability of enough electrolyzer units might prove to be a bottleneck for the process roll-out. 78 Further, the simplified approach for the integration scenarios, as described in Section 2.7.3, should only be understood as an approximation of the actual costs for the integration of fluctuating renewable energy sources. A more accurate process design would include a cost-optimised design of the power production system (mix of wind and PV), the electrolyzer and the hydrogen storage system depending on local boundary conditions.…”
Section: Methodsmentioning
confidence: 99%
“…The economic evaluation of the concept follows the approach of Peters, Timmerhaus, and West [26], which has been utilized in several previous techno-economic studies [15,27,28]. To apply this methodology, a database of reference equipment costs is needed to account for changes in the process configuration and its impact on capital and operational expenses.…”
Section: Techno-economic Analysismentioning
confidence: 99%
“…Furthermore, the increase of renewable energy in the electricity mix is required to achieve a positive environmental impact with the PBtL cases. Recent studies of Habermeyer et al [27] and Weyand et al [14] showed that utilizing the electricity from the German grid to generate the hydrogen, yields in an even higher greenhouse gas emission than using the fossil alternatives. Hence, PBtL concepts imply a potential alternative for an increased production of alternative fuels by an increased carbon efficiency but strongly depend on the availability of renewable and inexpensive electricity.…”
Section: Plant Location Germanymentioning
confidence: 99%
“…Biomass-to-Liquid (BTL): BTL SAF is derived from biomass feedstocks like wood, crop residues, or algae. These feedstocks are converted into liquid hydrocarbons through processes like pyrolysis or gasification (Habermeyer, et al,2023).…”
Section: Types and Sources Of Safmentioning
confidence: 99%
“…2. Lower Particulate and NOx Emissions: SAF also reduces emissions of particulate matter and nitrogen oxides (NOx) by 70% (Habermeyer, et al,2023) which have detrimental effects on air quality and human health. Lowering these emissions near airports and along flight routes improves local air quality and public health.…”
Section: Environmental and Economic Impacts 51 Reduction In Carbon Em...mentioning
confidence: 99%